Factors influencing companies to be public listed companies - Syazrul Afif Ismail @ Abdul Raof, 1994-, author 612057 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Perakaunan) - Universiti Teknologi Malaysia, 2018